User behaviour-based approach to define mobility devices needs of disabled person in Algeria: a questionnaire study - Bellal, Salah-Eddine; Leila-Hayet Mouss; Sahnoun, M’hammed; Messaadia, Mourad (Disability and Rehabilitation: Assistive Technology, 2020)
This article showcases the adaptability of existing mobility devices for the Algerian disabled population. It aims to develop a behavior model of disabled Algerian persons through (1) development of a theoretical model based on literature review and (2) improvement of this model by using local collected data from our developed questionnaire.